1996
DOI: 10.1063/1.363611
|View full text |Cite
|
Sign up to set email alerts
|

Composition effects on the crystal structure of CuInSe2

Abstract: By x-ray powder diffraction and the Rietveld refinement method, the atomic positions in CuInSe2 were determined for compositions close to stoichiometry. The Se position, x(Se), was found to be correlated to the Cu content. According to a model proposed by Jaffe and Zunger [Phys. Rev. B 29, 1882 (1984)], changes in x(Se) induce a variation in the optical band gap, Eg. This could explain the spread in energy gap, Eg, found by many authors for this compound. The increase in the lattice parameter, a, correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 32 publications
5
38
3
Order By: Relevance
“…Indeed, the dispersion of data for u is known to be large in CIGS compounds. 11,12 Concerning CZTS, fewer measurements can be found in literature and in most cases only a and c are reported. 13 Concerning the experimental band gaps, [14][15][16] early studies suggested a value of about 1.4-1.6 eV both for S and Se compounds.…”
Section: 8mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the dispersion of data for u is known to be large in CIGS compounds. 11,12 Concerning CZTS, fewer measurements can be found in literature and in most cases only a and c are reported. 13 Concerning the experimental band gaps, [14][15][16] early studies suggested a value of about 1.4-1.6 eV both for S and Se compounds.…”
Section: 8mentioning
confidence: 99%
“…In particular, for CuIn(S,Se) 2 , LDA and GGA yield structural internal parameters with an error of about 5% for u. 11,12,17 Such an error leads to an underestimate by more than 50% of the band gap in a calculation at the theoretical geometry.…”
Section: 8mentioning
confidence: 99%
“…[21][22][23][24][25] Under high pressure it may transform to a NaCl-type structure with higher coordination. 26 On release of the pressure, a metastable zinc blende-type structure may be produced as an intermediate phase before the stable chalcopyrite structure is restored at ambient pressure.…”
Section: Structure Identification Of the Cu 2 Se And Cis Phasesmentioning
confidence: 99%
“…The samples with a copper deficit and with a deviation from ideal Se content have been studied in [15] and [16], respectively. Offstoichiometric samples have also been studied, e.g.…”
Section: Introductionmentioning
confidence: 99%